The first-in-class ERK inhibitor ulixertinib shows promising activity in mitogen-activated protein kinase (MAPK)-driven pediatric low-grade glioma models - Romain Sigaud; Lisa Rösch; Charlotte Gatzweiler; Julia Benzel; Laura von Soosten; Heike Peterziel; Florian Selt; Sara Najafi; Simay Ayhan; Xenia F. Gerloff; Nina Hofmann; Isabel Büdenbender; et al. (2022)
Abstract Background Pediatric low-grade gliomas (pLGG) are the most common pediatric central nervous system tumors, with driving alterations typically occurring in the MAPK pathway. The ERK1/2 inhibitor ulixertinib (BVD-523) has shown promising responses in adult patients with mitogen-activated protein kinase (MAPK)-driven solid tumors. Methods We investigated the antitumoral activity of ulixertinib monotherapy as well as in combination with MEK inhibitors (MEKi), BH3-mimetics, or chemotherapy in pLGG. Patient-derived pLGG models reflecting the two most common alterations in the disease, KIAA1549:BRAF-fusion and BRAFV600E mutation (DKFZ-BT66 and BT40, respectively) were used for in vitro and in vivo (zebrafish embryos and mice) efficacy testing. Results Ulixertinib inhibited MAPK pathway activity in both models, and reduced cell viability in BT40 with clinically achievable concentrations in the low nanomolar range. Combination treatment of ulixertinib with MEKi or BH3-mimetics showed strong evidence of antiproliferative synergy in vitro. Ulixertinib showed on-target activity in all tested combinations. In vivo, sufficient penetrance of the drug into brain tumor tissue in concentrations above the in vitro IC50 and reduction of MAPK pathway activity was achieved. In a preclinical mouse trial, ulixertinib mono- and combined therapies slowed tumor growth and increased survival. Conclusions These data indicate a high clinical potential of ulixertinib for the treatment of pLGG and strongly support its first clinical evaluation in pLGG as single agent and in combination therapy in a currently planned international phase I/II umbrella trial.